Search for rare decays of the Z and Higgs bosons to a J/ψ or ψ(2S) meson and a photon in proton-proton collisions at s=13TeV - A. Hayrapetyan; A. Tumasyan; W. Adam; J.W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P.S. Hussain; M. Jeitler; N. Krammer; A. Li; et al. (Physics Letters B)
A search is presented for rare decays of the Image 1 and Higgs bosons to a photon and a Image 2 or a Image 3 meson, with the charmonium state subsequentially decaying to a pair of muons. The data set corresponds to an integrated luminosity of 123fb−1 of proton-proton collisions at a center-of-mass energy of 13 TeV collected with the CMS detector at the LHC. No evidence for branching fractions of these rare decay channels larger than predicted in the standard model is observed. Upper limits at 95% confidence level are set: Image 4, Image 5, Image 6, and Image 7. The ratio of the Higgs boson coupling modifiers Image 8 is constrained to be in the interval (−157,+199) at 95% confidence level. Assuming Image 9, this interval becomes (−166,+208).